2021
DOI: 10.1017/cjn.2021.12
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Spasms and Trisomy 21: Unfavorable Outcomes with First-line Vigabatrin Therapy

Abstract: Introduction: Among children with infantile spasms (ISs), those with trisomy 21 (T21) and those with normal development at onset and no identifiable etiology (previously referred to as “idiopathic”) are expected to have relatively favorable outcomes. The study objective is to determine if differences exist in treatment response, relapse, and subsequent epilepsy between these two groups when vigabatrin is used as first-line treatment. Methods: In this retrospective study, patients were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This is comparable to the results of Armstrong et al (n=20) and the ICISS Down syndrome subgroup analysis (n=37), with rates of 60% and 54% respectively. 17,18 Vigabatrin was the second most common first-line agent, with cessation of spasms in 28% (5 out of 18), similar to the 21% (5 out of 24) success rate reported by Datta et al 19 Our findings are also in agreement with the ICISS cohort, who reported the addition of vigabatrin was beneficial in only 1 out of 7 who did not respond to first-line prednisolone. 17,18 Only six children had both combination prednisolone and vigabatrin as first-line treatment in our cohort, with an 80% response although three out of six developed side effects, including one who required admission to an intensive care unit.…”
Section: Discussionsupporting
confidence: 90%
“…This is comparable to the results of Armstrong et al (n=20) and the ICISS Down syndrome subgroup analysis (n=37), with rates of 60% and 54% respectively. 17,18 Vigabatrin was the second most common first-line agent, with cessation of spasms in 28% (5 out of 18), similar to the 21% (5 out of 24) success rate reported by Datta et al 19 Our findings are also in agreement with the ICISS cohort, who reported the addition of vigabatrin was beneficial in only 1 out of 7 who did not respond to first-line prednisolone. 17,18 Only six children had both combination prednisolone and vigabatrin as first-line treatment in our cohort, with an 80% response although three out of six developed side effects, including one who required admission to an intensive care unit.…”
Section: Discussionsupporting
confidence: 90%
“…In the literature, there appears to be a marginally more favorable outcome with the use of hormonal therapy first-line for epileptic spasms in trisomy 21. 22 -24 However, no large trials have been performed. It is known that children with trisomy 21, and those with normal development at onset and no identifiable etiology (previously referred to as “idiopathic”), are expected to have relatively favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%